THE BIOTECHNOLOGICAL ASPECTS OF WHEY PROTEINS HYDROLYSATE ANTIOXIDANT ACTIVITY INCREASING IN THE DIGESTION MODEL - Elena Vladimirovna Budkevich; Roman Olegovich Budkevich; Aleksey Alekseyevich Martak; Nikita Mikhaylovich Fedortsov; Anastasiya Igorevna Eryomina (Современная наука и инновации)
In the modeling of digestion using the complex of pepsin and pancreatin on protein substrates (KSB80, ISB90, ISB95) the most antioxidant activity have demonstrated ISB95 in a minimal time (30 minutes), which allows using it as a functional additive for increasing the final product antioxidant activity in the technological process.